Istinbath Methodology of DSN-MUI: Integrating Classical Islamic Jurisprudence with Contemporary Needs - Mubarak, Jaih; Mahfudz, Shaifurrokhman (Universitas Muhammadiyah Surakarta, 2024)
The objective of this paper is to examine the methodology employed by the National Sharia Board of the Indonesian Council of Ulama (DSN-MUI) in deriving legal rulings (istinbath) within the dynamic framework of the intersection between classical Islamic jurisprudence and contemporary societal needs. The study seeks to provide a detailed analysis of the approach adopted by the DSN-MUI, with a particular emphasis on its predominant utilization of the Intiqa’i or Takhyiri framework. This approach underscores the significance of considering maslaha (public interest) and makharij (solutions) over tarjih (preferential selection based on the strongest evidence). Employing a qualitative research methodology, the paper conducts a thorough content analysis of the fatwas issued by the DSN-MUI and relevant scholarly literature to delve into their istinbath process. The research findings suggest that the DSN-MUI occasionally resorts to collective ijtihad (ijtihad jama’i) in exceptional circumstances, diverging from the prevailing consensus on issues such as non-cash gold transactions and the conversion of tabarru’ contracts into mu`awadhat contracts. By shedding light on the application of the principles of tafriq al-halal wa-al-haram (differentiation between what is permissible and impermissible) and al-’ibrah fi al-’uqud bi al-alfazh wa al-mabani (legal reasoning in accordance with the teachings of Imam Shafii), this study significantly contributes to the field of Islamic jurisprudence. Moreover, this research offers a comprehensive analysis of the istinbath methodology of the DSN-MUI, providing valuable insights into how classical Islamic jurisprudence is adapted to address contemporary economic and social challenges in the Indonesian context.